Assessment Overview: A guide to various kinds and reasons for assessment before, during, and after teaching - Grier, Jeanne (Allies for Education, 2019)
This presentation provides an introductory guide for key terms often used when discussing assessment practices in schools, as well as reasons for conducting learning assessments. Distinctions are made between assessments, measurements, and evaluations as a framework for beginning the overview. The presentation ends with putting assessments in the context of instruction and their relation to learning objectives and instructional practices.